1993
DOI: 10.1067/mva.1993.45736
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal venous aneurysm: Report of two cases and review of the world literature

Abstract: These data substantiate the impression that the Health Care Finance Administration has substantially undervalued the costs of performing duplex scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The cause of venous aneurysms remains unknown, although several theories have been proposed. Lev and Saphir characterized the structural changes that occurred with age and concluded that there are two changes that can lead to aneurysm formation: endophlebohypertrophy [8] (progressive intimal proliferation of elastic, muscle, and connective tissue), which occurs as a normal response to mechanical stress; and endophlebosclerosis (a degenerative pathologic process characterized by alterations in ground substance, disruption and loss of elastic fibers, loss of medial muscle cells, and fibrosis) [11] . This results from the pressure exerted by the adjacent arterial wall and the flow disturbance produced by continuous pulsations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cause of venous aneurysms remains unknown, although several theories have been proposed. Lev and Saphir characterized the structural changes that occurred with age and concluded that there are two changes that can lead to aneurysm formation: endophlebohypertrophy [8] (progressive intimal proliferation of elastic, muscle, and connective tissue), which occurs as a normal response to mechanical stress; and endophlebosclerosis (a degenerative pathologic process characterized by alterations in ground substance, disruption and loss of elastic fibers, loss of medial muscle cells, and fibrosis) [11] . This results from the pressure exerted by the adjacent arterial wall and the flow disturbance produced by continuous pulsations.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory claims that complete absence of medial smooth muscle is clearly congenital [11] . This has been associated with decreased amounts of smooth muscle cells and elastin fibers, fibrous connective tissue and elastic fibers in the vein wall [12] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations